RESEARCH OF THE AVIATION FUELS BIODESTRUCTION MECHANISM - Безпальчук, О. В.; Шкільнюк, І. О.; Бойченко, С. В. (Science-based technologies, 2013)
The work on the study of microorganisms capable of biological destruction of aviation fuels. You are a scientist mechanism of degradation of petroleum hydrocarbons. Investigated and analyzed the conditions favorable for growth and reproduction of microorganisms-destructors.